Antegrade versus retrograde locked intramedullary nailing for femoral fractures: which is better? - Yu, C.K.; Singh, V.A.; Mariapan, S.; Chong, S.T.B. (2007)
Background: Locked intramedullary nailing or interlocking nailing (ILN) is a proven mode of treatment for femoral shaft fractures. It can be inserted via the antegrade or retrograde approach. Retrograde approach is technically less demanding especially if the patient is overweight. But there are concerns with regard to the violation of the knee and its effect on subsequent knee function. Methods: We studied consecutive cases of femoral shaft fractures treated with locked intramedullary nailing at the Penang General Hospital, from 1st June 2004 to 1st June 2005. We looked at radiological and clinical union rates, union of fractures, alignment of the operated limb, and the knee function, using the Thoresen scoring system. Results: There were a total of 77 cases of femoral interlocking nails during the study period. Forty-two cases were antegrade nails and 35 cases were retrograde nails. Both groups of patients eventually achieved union of the fracture and retrograde nailing group showed significantly earlier union rate (p = 0.032). There is no significant difference between both groups, in regards to knee pain, swelling, and range of motion as well as postnailing femoral alignment. Conclusions: Both methods of nailing achieved excellent union rates with good alignment of the limb. Contrary to popular belief, we found that retrograde nailing does not give rise to a higher rate of knee complications. Therefore, we strongly recommend this approach of nailing as it is technically less demanding.